Synthesis, characterization, and biological evaluation of some novel ϒ-aminobutyric acid aminotransferase (GABA-AT) inhibitors - Shrivastava, Sushant Kumar; Sinha, Ojaswi; Kumar, Munish; Waiker, Digambar Kumar; Verma, Akash; Tripathi, Prabhash Nath; Bhardwaj, Bhagwati; Saraf, Poorvi (Springer, 2022)
In our present work, some novel substituted 4-phenyl-5-vinylpyrrolidin-2-one derivatives were designed, synthesized, and evaluated for their γ-aminobutyric acid-aminotransferase (GABA-AT) inhibition and in-vivo anticonvulsant activity. Among all the synthesized derivatives, compound 7f was observed as the most potent and competitive inhibitor of GABA-AT (IC50 = 46.29 ± 3.19 µM, Ki = 0.106 ± 0.004 μM). The in-vivo anticonvulsant activity against maximum electroshock (MES) and PTZ, induced seizures test of compound 7f, was observed very significantly (P < 0.05) in comparison with standard Vigabatrin and have shown an increase in the level of GABA in the cortex region of the brain. The ex-vivo studies have also suggested reduced tissue necrosis. Finally, In-silico molecular docking and dynamics studies of compound 7f have shown that it forms desired amino acid residue interactions with the GABA-AT and was stable for 50 ns in the active site pocket of the enzyme.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Anti-Epileptic Drugs; Epilepsy; GABA-AT Inhibitors; Vigabatrin